Analisis Keuangan dan Perencanaan Bisnis: Kasus Bengkel Wahda Pringapus - Zega, Aliasa; Maria Th, Alleta Dewi (Mahesa Research Center, 2024)
This article aims to analyze financial performance and develop a strategic business plan for Bengkel Wahda Pringapus, a small and medium-sized enterprise (SME) in the automotive repair sector. The primary issues are the lack of structured financial planning and optimal business strategy, which limits growth potential amidst competition with modern repair shops that utilize the latest technology. The study draws on financial analysis and business planning theories to address these challenges, including the Balanced Scorecard and human resource management. Data were collected through semi-structured interviews and direct observation and then analyzed qualitatively. The findings indicate that strategies focused on service quality improvement and adopting simple technologies have significantly enhanced Bengkel Wahda’s financial performance, evidenced by annual revenue growth of 15%. This study recommends further expansion of these strategies to maintain competitiveness in the future, including human resource development and adopting more efficient technologies.